Unmet needs for information and psychosocial support in relation to quality of life and emotional distress: a comparison between gynecological and breast cancer patients - Faller, Hermann; Keller, Monika (Patient education and counseling, 2017)
We compared gynecological and breast cancer patients regarding their needs for information and psychosocial support, quality of life (QoL), and emotional distress and the relationship among these constructs.